KNOWLEDGE AND BEHAVIOR TO PREVENT PULMONARY TUBERCULOSIS TRANSMISSION - Silvia Putri Arifah; Umi Faridah; Sukarmin Sukarmin (Universitas Muhammadiyah Kudus, 2025)
Indonesia continues to face major challenges in controlling pulmonary tuberculosis (TB) transmission, with high rates of new cases often linked to inadequate prevention practices such as poor mask compliance, lack of cough etiquette, and insufficient household ventilation, which significantly increase transmission risk within families. This study aimed to analyze the relationship between knowledge and behavior in preventing pulmonary TB transmission at the Kaliwungu Community Health Center. A cross-sectional descriptive design was used with purposive sampling, involving 57 respondents who met the inclusion criteria: patients who tested positive for pulmonary TB, were registered at the Kaliwungu Community Health Center, resided in Kaliwungu District, were aged ≥18 years, and fully conscious during data collection. Exclusion criteria were patients who had recovered, those with TB-HIV or MDR-TB, and respondents who did not complete the questionnaire correctly. Data were collected using a structured questionnaire on TB knowledge and prevention behaviors, then analyzed using univariate analysis and chi-square tests for bivariate analysis. The results revealed a significant relationship between knowledge and prevention behavior (p=0.009; OR=6.000), indicating that respondents with higher knowledge were six times more likely to engage in preventive actions compared to those with lower knowledge. These findings emphasize the critical role of patient knowledge in shaping behavior, suggesting that improving health literacy about pulmonary TB can directly strengthen prevention practices. In conclusion, the study demonstrates a significant association between knowledge and prevention behaviors, highlighting the need for targeted educational interventions to reduce TB transmission at the community level..